COVID-19 in acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS): a propensity matched analysis (2020-2021) - Sivasubramanian, Barath Prashanth; Joshi, Shashvat; Ravikumar, Diviya Bharathi; Madhumithaa Jagannathan,; Babu, Sonia; Sripathi, Shanthi Reddy; Javvaji, Avinash; Jain, Priyanshu; Kumar Shanmugam, Dinesh; Swami Kannan, Bharath Duraisamy; Tirupathi, Raghavendra; Dalal, Rutul (Frontiers in Oncology, 2024)
BackgroundBy 2023, COVID-19 had caused 6.8 million deaths in the United States. COVID-19 presents more severely in leukemia compared to solid tumors (OR 1.6, p<0.05). However, data on Acute Myeloid Leukemia (AML) and Myelodysplastic Syndrome (MDS) are limited. We investigated the mortality in AML and MDS patients with COVID-19.MethodsData from the 2020-2021 National Inpatient Sample was used to conduct a cross-sectional analysis. We identified AML and MDS patients with COVID-19 hospitalizations through ICD-10 codes. Analysis was done by propensity matching and multivariate regression with a p-value of ≤0.05.ResultsOf 28,028 AML admissions, 336 (1.2%) were admitted for COVID-19. AML-COVID-19 cohort had a lower hospitalization risk (aOR 0.3, p=0.000) and higher mortality (21.7% vs 8.7%; aOR 1.6, p=0.023) than AML patients admitted for other causes. AML patients post-HSCT (Hematopoietic Stem Cell Transplantation) had a higher risk of COVID-19 (20.2% vs 9.8%; aOR 2.6, p=0.000) and increased mortality (19.1% vs 6.7%; aOR 4.1, p=0.000) compared to other causes. Similarly, of 28,148 MDS patients, 769 (2.7%) were admitted for COVID-19. The MDS-COVID-19 cohort had a lower hospitalization risk (aOR 0.59, p=0.000) and higher mortality (19.6% vs 6.6%; aOR 2.2, p=0.000) compared to other causes. In MDS, HSCT did not alter the risk of COVID-19 hospitalizations (3% vs 3.9%; aOR 0.9, p=0.662), but these patients had higher mortality (17.4% vs 5.1%; aOR 4.0, p=0.032).ConclusionCOVID-19 hospitalization was low in AML and MDS but carried a high mortality risk. Post-HSCT, the mortality is high, warranting research into understanding the underlying factors.